Bond Coefficient kb of Concrete Beams Reinforced with GFRP, CFRP, and Steel Bars - Kabashi, Naser; Këpuska, Arbër; Krasniqi, Enes; Avdyli, Besart (Salehan Institute of Higher Education, 2021)
There are several reasons why civil and structural engineers should use Fiber Reinforced Polymer bars in concrete. The primary reason is durability, and other relevant parameters, high strength and, lightweight. Non-corrosive attributes make their use particularly suitable in different situations. Due to low elastic modulus and poor bonding, the use of Fiber Reinforced Polymer results in larger crack widths under serviceability limit state especially beams reinforced with glass fiber bars. The study purpose of this paper is to investigate the kb values. The methodology of this paper is comparing the analytical and experimental results. The investigation included 12 beams, using the four-point load test. The geometrical parameters of tested beams with dimensions: 130×220×2200 mm, reinforced with different diameters, helically-grooved glass fiber bars, and sand-coated carbon fiber bars. The measured cracks were used to assess the current kb values recommended in the design codes and guides. The findings did not support the use of the same kb value for different bars because, in addition to the type of bar, the value of kb is also affected by the type of surface and the diameter of the bar. What is observed based on results shows that CFRP bars have a more constant value depending on the diameter, while GFRP bars have large value changes depending on the diameter. Doi: 10.28991/cej-2021-03091722 Full Text: PDF